CREATING AN ENGLISH MATERIALS IN ORAL DISCOURSE ASPECT FOR THE TAXI DRIVERS - Dewa Ayu Kadek Claria (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2020)
This research was concerned in creating an English material in oral discourse aspect for the Taxi Drivers. The research conducted based on the problems faced by the taxi drivers in the tourism object which need English as a main language in communicating with the international passenger. The improvement in English skill especially in oral discourse for the taxi drivers was aimed to provide a better service in their job which runs in tourism field. The method used in conducting the research consists of three steps; they are chose the data source, collect the data, and analyse the data. The data was taken by doing the interview and spread the questionnaire to the taxi drivers in Sanur. The material selection was done by selecting the most difficult aspect that the drivers thought in learning English especially in oral discourse aspect. The analysed data provide the basis in creating an English material for the drivers. The theory applied in this research are theory of Hutchinson and Waters in their book entitled English for Specific purpose (1987) as the main theory and the theory of Van Dijk (1993) in his book entitled Principles od Discourse analysis and Searle, J. R. (1696) in her book entitled Speech Acts, an essay in the philosophy of language as supporting theories. As the result, the English materials was created based on Hutchinson and Waters theory which consists of input, content focus, language focus and task. Those model of learning was the most suitable to the taxi driver seen from the layout and also the English material has more specific material organization by applied this model.